Overview of the Level of Knowledge of Darmo Medan Health College Students Regarding Excellent Service in Increasing Patient Satisfaction - Aisyah Daulay, Cahya; Budiarti, T (Jurnal Kesmas Prima Indonesia, 2025)
Health facilities are providers of health services to improve the community's health. The quality of health services influences patient satisfaction with health facilities. Excellent service is oriented towards patient satisfaction, so health workers must provide optimal service. Patient experience with the services offered influences the choice of health facilities for their treatment. Patient satisfaction with health services is an evaluation of health facility management in maintaining or improving the quality of health services. This study aims to determine the level of student knowledge about excellent service for patients at STIKes Darmo Medan Rahun 2024. The results of the study showed that excellent service was measured using 6 indicators, namely attitude (Attitude), attention (Attention), action (Action), ability (Ability), appearance (appearance), and responsibility (accountability) in the less category.